2015
DOI: 10.1111/gcbb.12256
|View full text |Cite
|
Sign up to set email alerts
|

Application of a process‐based model for predicting the productivity of Eucalyptus nitens bioenergy plantations in Spain

Abstract: The feasibility of using plantation-grown biomass to fuel bioenergy plants is in part dependent on the ability to predict the capacity of surrounding forests to maintain a sustainable supply. In this study, the potential productivity of Eucalyptus nitens (Deane and Maiden) Maiden plantations grown for bioenergy in a region of north-west Spain was quantified using the 3-PG process-based model. The model was calibrated using detailed measurements from five permanent sample plots and validated using data from thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
1
7
1
3
Order By: Relevance
“…In this study, at 7,500 trees ha -1 E. camaldulensis and E. nitens showed the highest average yield (22.5 and 35.2 Mg ha -1 ) 48 months after the establishment of the trials. In turn, (González-García et al, 2016a) reported an annual production of only 13.7 Mg ha -1 (lower than that found herein) seven years after establishing the plantation. According to Sochacki et al (2007), E. globulus plantations at 4,000 trees ha -1 accumulated 16.6 Mg ha -1 of dry material after the plantation's third year.…”
Section: Discussioncontrasting
confidence: 85%
“…In this study, at 7,500 trees ha -1 E. camaldulensis and E. nitens showed the highest average yield (22.5 and 35.2 Mg ha -1 ) 48 months after the establishment of the trials. In turn, (González-García et al, 2016a) reported an annual production of only 13.7 Mg ha -1 (lower than that found herein) seven years after establishing the plantation. According to Sochacki et al (2007), E. globulus plantations at 4,000 trees ha -1 accumulated 16.6 Mg ha -1 of dry material after the plantation's third year.…”
Section: Discussioncontrasting
confidence: 85%
“…The inclusion of these parameters confirms the fact that E. nitens growth is affected by climate factors in summer: Although annual total precipitation in the area is approximately 1,250 mm, well within the requirements for the species, which have been established as between 750 and 1,750 mm year -1 (FAO 1981;Booth and Pryor 1991), rainfall in the study area is in fact considerably reduced in summer, which can affect tree growth, as has been shown in another study on the same permanent sample plots (González- García et al 2015). Moreover, higher summer temperatures increase tree evapotranspiration, which together with the reduction in soil water content, means that growth is likely to be negatively affected in this season.…”
Section: Development Of Growth Models Including Environmental Datasupporting
confidence: 71%
“…Predictions of plantation growth at plot scale using 3‐PG are useful, and species‐specific growth parameters are required, as has been shown in other studies of eucalypt plantations in Brazil and other countries (Stape et al, ; Almeida et al, , ; Fontes et al, ; Almeida and Sands, ). Spatial applications also have been used elsewhere (Coops and Waring, ; Tickle et al, ; Almeida et al, ; González‐García et al, ), and the model is used for research and operations by some forest plantation companies (Almeida et al, ; Almeida et al, ). However, 3‐PG integration with a hydrological model (TOPMODEL) allows predictions of water balance at catchment scale that can take account of different land‐use and management options.…”
Section: Discussionmentioning
confidence: 99%